Evaluation of Transverse strength, Impact strength and Hardness of Thermosense denture base material and compare the result with heat cure acrylic denture base material (in vitro study) (Mustansiria Dental Journal, 2019)
Background: Thermosense material is the innovative virtually unbreakable, newmonomer free rigid denture base material easy and quick to polish and availablein 10 colors, suitable to patients unable to accept denture made from materialsthat could result in allergic reactions or other sensitivity problems. This type issuitable for full and partial denture and can be used for rebase and reline jobs.Also suitable for overdenture on implant and for repair.Material and methods: sixty samples were prepared and divided in to two maingroups according to the type of material that used (thermosense denture basematerial and heat cure acrylic denture base material). Each main group weresubdivided in to three subgroups according to the type of test that has used(Hardness, impact strength, and transverse strength). Data were analyzed by onewayanalysis of t-test.Results: for this study the result for three tests; hardness, transverse strength andimpact strength show high significant difference.conclusion: This study showed Thermosense denture base material had higher impactstrength than Heat cure acrylic denture base material but this material had highertransverse strength and hardness than Thermosense denture base material.